Autobiography of Quṭb Al-Din Shīrāzī (a Persian physician in 14th century AD) in his manuscript, Al-Tuḥfa Al-Sa'Dīya : Autobiografija Quṭb Al-Din Shīrāzīa (perzijski liječnik u 14. stoljeću) u njegovu rukopisu, Al-Tuḥfa Al-Sa'Dīya - Arezaei, Hamed (Array, 2021)
Quṭb al-Din Shīrāzī (1236-1311 AD), the Persian polymath had great contributions to the fields of philosophy, mathematics, medicine, astronomy, music, literature, and Islamic studies. He lived during the Ilkhanid kingdom in Iran. He wrote an autobiography in the preface of his medical manuscript, al-Tuḥfa al-Sa"dīya. He discussed his views on science and then, he explained his life story, in particular his education and contribution to science. He mentioned the reasons that led him to write al-Tuḥfa al-Sa"dīya, his main medical work. As a great polymath, he traveled to many countries, and his words cleared the scientific atmosphere of 14th century AD. Also, he directly introduced his teachers and their abilities and works. Furthermore, scientists who worked on the Canon of Medicine had commentaries on this book, which were comprehensively introduced in this autobiography.